Distinct roles for dynein light intermediate chains in neurogenesis, migration, and terminal somal translocation - Gonçalves, João Carlos (2019)
Cytoplasmic dynein participates in multiple aspects of neocortical development. These include neural progenitor proliferation, morphogenesis, and neuronal migration. The cytoplasmic dynein light intermediate chains (LICs) 1 and 2 are cargo-binding subunits, though their relative roles are not well understood. Here, we used in utero electroporation of shRNAs or LIC functional domains to determine the relative contributions of the two LICs in the developing rat brain. We find that LIC1, through BicD2, is required for apical nuclear migration in neural progenitors. In newborn neurons, we observe specific roles for LIC1 in the multipolar to bipolar transition and glial-guided neuronal migration. In contrast, LIC2 contributes to a novel dynein role in the little-studied mode of migration, terminal somal translocation. Together, our results provide novel insight into the LICs' unique functions during brain development and dynein regulation overall.